If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -12 = 8x + 16 Reorder the terms: -12 + x = 8x + 16 Reorder the terms: -12 + x = 16 + 8x Solving -12 + x = 16 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -12 + x + -8x = 16 + 8x + -8x Combine like terms: x + -8x = -7x -12 + -7x = 16 + 8x + -8x Combine like terms: 8x + -8x = 0 -12 + -7x = 16 + 0 -12 + -7x = 16 Add '12' to each side of the equation. -12 + 12 + -7x = 16 + 12 Combine like terms: -12 + 12 = 0 0 + -7x = 16 + 12 -7x = 16 + 12 Combine like terms: 16 + 12 = 28 -7x = 28 Divide each side by '-7'. x = -4 Simplifying x = -4
| Ln(2x^2-1)=0 | | -3(n-8)=-3+6n | | 2y+12(4)+4(3)=16 | | 4.39N+3.44N=66.44 | | 5y^2-10x=4 | | =12L | | 3e^4x=26 | | 2n^0*3n= | | x(5-x)=-6 | | (3-7)= | | x-30=46 | | x^2+5x-2=3x+6 | | 4s^2+4s^2= | | f(z)=4x-1 | | 5*x^2=2x | | 5x*2=2x | | 10x-17=9x+5 | | 335-x=15 | | 4s^2+4s^2+6s-1+8-5s= | | 2+12=5+-9 | | 10x^2+40x-2000=0 | | 15a+3=33 | | 2x+12=5-9 | | 7(4p+2q+3r)= | | 29=5-3x | | 7x-(7+4x)= | | -8(u+5)=-64 | | 5x+5=2x-x+8 | | =(2n+14)-10 | | 4(3x+5)=34 | | 52x+13=3(x-12) | | -2(5y+-3)=56 |